COVID-19 Entwined the Dynamic Relationship between Stock Returns and Macroeconomic Variables - Malik, Amina; Butt, Babar Zaheer; Aziz, Haroon (Information Management and Business Review, 2022)
This study examines the dynamic relationship between macroeconomic variables and stock prices in Pakistan in the COVID-19 pandemic scenario. For this purpose, monthly data has been taken from Jan 2019 to June 2021 and divided into Pre-COVID, COVID and overall periods. Data have been retrieved from various sources including Statistical Reviews & Bulletins of State Bank of Pakistan, Karachi Stock Exchange and Pakistan Economic Survey. To assess the relationship between economic variables and stock prices, Cointegration, Granger-causality and Impulse Repose Function Tests have been applied on three data series. The results of the study reveal that there is a long-term equilibrium relationship between all economic variables and stock prices in the Pre-COVID period. However, most of the economic variables do not have such a relationship during the COVID period and the pattern of the relationship is almost the same in the overall period. Even the short-run dynamic relationship between economic variables and stock returns is affected by the pandemic. The results show that economic variables affect stock returns differently in the COVID situation than in the Pre-COVID scenario and it also affects the short-run relationship in the overall period. This research study provides imminent findings on the linkage between macroeconomic variables and stock prices in the Pakistani context. It helps investors and regulators in customizing their decisions and macroeconomic regulations respectively to improve the financial and economic stability of the country in the wake of the pandemic.